CONTACT AND ENDOGENOUS MODERNIZATION OF A TRADITIONAL STATE: BUKHARA UNDER MUZAFFAR AND ABDULAHAD - Облобердиев Ж. К. (TARIXIY TADQIQOTLAR, 2026)
The article presents a comparative analysis of reforms in the Bukhara Emirate during the reigns of two successive rulers – Emir Muzaffar (1860–1885) and Emir Abdulahad (1885–1910). Based on the analysis of Eastern chronicles, Ahmad Donish’s writings, Russian administrative records, and modern historiography, the study reconstructs the yearly steps of modernization across four key sectors: state administration, taxation, military organization, and the socio-cultural sphere. The results demonstrate that under Muzaffar, modernization developed as an endogenous rationalization of political consciousness focused on the functional meaning of power, while under Abdulahad it took an instrumental bureaucratic form – through fixed registration of decisions, formal instructions, reporting, and control. Thus, the two reigns represent a dual model of evolutionary modernization of a traditional state: from the idea of rational governance to the mechanism of rational governance.